Effect of volume of the solution and sulfurization on properties of Cu2ZnSnS4 thin films fabricated by spray assisted chemical vapour deposition method. (16th April 2022) - Bouzida, Samira; Battas, Manale; Benamar, El Bachir; Schmerber, Guy; Dinia, Aziz; Abd-Lefdil, Mohammed; Regragui, Mohammed
ABSTRACT: Cu2 ZnSnS4  thin films were produced by spray assisted chemical vapor deposition process (SACVD) technique using different volumes of aqueous ionic solution, followed by sulfurization in sulfur vapors at 500°C and under Argon atmosphere. These CZTS thin films were analysed by X-ray diffraction and Raman scattering analysis that have confirmed the kesterite phase structure of CZTS films before and after sulfurization. The optimum band gap of the as-deposited CZTS films are between 1.40 and 1.43 eV. The cristallinity of the layers improve after sulfurization and their band gap varies between 1.44 and 1.50 eV. The surface morphology of the samples was examined by scanning electron microscopy. The chemical composition was determined by energy dispersive X-ray spectroscopy which shows the formation of Cu poor and Zn rich sulfurized CZTS thin films. Hall Effect measurements revealed that all the films before and after sulfurization are p-type. The sulfurized films obtained in our laboratory have carrier concentrations ranging from 3.1 to 6.8 x 10 18  cm -3, a resistivity between 0.199 and 0.262 Ω.cm and mobility between 3.5 and 10.1 cm 2 /V.s.